Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1262/jrd.2021-052
|View full text |Cite
|
Sign up to set email alerts
|

Predisposing factors, diagnostic and therapeutic aspects of persistent endometritis in postpartum cows

Abstract: A certain level of endometrial bacterial infection and inflammation is involved in bovine uterine involution during the puerperal period. Factors that hamper normal uterine involution expose the uterine environment to pathological conditions, causing different endometritis levels. The lack of proper diagnostic tools extends the time to conception. Efforts have been made to elucidate the postpartum uterine environment, including bacterial flora, changes in transient endometrial inflammation, and the pathophysio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 80 publications
0
4
0
Order By: Relevance
“…Endometritis is inflammation of the endometrial lining of the uterus. Endometritis generally occurs after 20 days postpartum, very abnormal parturition (Rouse et al, 2019), such as abortion, retained placenta, premature birth, multiple births, dystocia, and injuries caused by tools used during less clean births (Osawa, 2021). Fetal death, seasonal factors, and bacterial infections were factors for endometritis in smallholder dairy farms (Lee et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Endometritis is inflammation of the endometrial lining of the uterus. Endometritis generally occurs after 20 days postpartum, very abnormal parturition (Rouse et al, 2019), such as abortion, retained placenta, premature birth, multiple births, dystocia, and injuries caused by tools used during less clean births (Osawa, 2021). Fetal death, seasonal factors, and bacterial infections were factors for endometritis in smallholder dairy farms (Lee et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…According to individual authors (Pascottini et al, 2017;Wagener et al, 2021), from 14 to 40 % of calving cows are characterized by postpartum inflammation of the endometrium, which occurs in 21 or more days after calving (Sheldon et al, 2006). Other studies have found (Dubuc et al, 2010;Bradford et al, 2015;Osawa, 2021) that in some cases, postpartum endometritis occurs in 50 to 90 % of cows.…”
Section: Postpartum Pathology Of the Uterusmentioning
confidence: 99%
“…In addition to metabolism, genital tract microbiota has an essential effect in the occurrence and development of endometritis (Osawa, 2021 ). A previous study showed that mice with endometritis had increased relative abundances of Klebsiella , Lachnoclostridium_5 and Citrobacter , which may be responsible for endometritis (Dong et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%